Comparative Analysis of Experimental Methods for Determining the Curie Temperature of Ferrite Materials - Bobuyok S. A. Sergey Andreevich; Surzhikov A. P. Anatoly Petrovich; Nikolaev E. V. Evgeny Vladimirovich; Malyshev A. V. Andrei Vladimirovich; Lysenko E. N. Elena Nikolaevna (2024, 2024)
We studied magnetic phase transitions near the Curie temperature in the ferrite material with the composition Ni0.4Zn0.6Fe2O4 using thermomagnetometric analysis and methods for recording the temperature dependences of initial magnetic permeability μ0(T) and specific electrical resistivity ρ(T). The study provides a description of the equipment used and the key features of the experimental methods under consideration. During thermomagnetometric analysis in the cooling phase, it has been found that the temperature at which the material completes its transition to the ferrimagnetic state corresponds to the inflection point on the μ0(T) curve and the break point on the ln⁡ρ(T) dependence graph. The established interaction between the parameters of transition processes may be useful for more accurate determination of the Curie temperature in ferrites